2016
DOI: 10.1007/s12020-016-0953-2
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of thyroid follicular neoplasms: results of a retrospective analysis of a large clinical series

Abstract: The most appropriate surgical management of "follicular neoplasm/suspicious for follicular neoplasm" lesions (FN), considering their low definitive malignancy rate and the limited predictive power of preoperative clinic-diagnostic factors, is still controversial. On behalf of the Italian Association of Endocrine Surgery Units (U.E.C. CLUB), we collected and analyzed the experience of 26 endocrine centers by computerized questionnaire. 1379 patients, surgically treated after a FN diagnosis from January 2012 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…We believe surveillance is sufficient to prevent missing lethal cancers because long term follow‐up of patients not only prevents overtreatment but also confirms the benign diagnosis. Diagnostic lobectomy for FN/SFN nodules increases the risk of treatment‐related complications, which should be avoided, and Conzo et al reported that 15.1% of 1379 patients treated with thyroidectomy for FN/SFN nodules in 26 Italian hospitals had surgery‐related complications. Do not harm patients is the first and most important element in Asian clinical practice, similarly emphasised in western practice …”
Section: Handling Of Niftp In Asian Practicementioning
confidence: 99%
See 2 more Smart Citations
“…We believe surveillance is sufficient to prevent missing lethal cancers because long term follow‐up of patients not only prevents overtreatment but also confirms the benign diagnosis. Diagnostic lobectomy for FN/SFN nodules increases the risk of treatment‐related complications, which should be avoided, and Conzo et al reported that 15.1% of 1379 patients treated with thyroidectomy for FN/SFN nodules in 26 Italian hospitals had surgery‐related complications. Do not harm patients is the first and most important element in Asian clinical practice, similarly emphasised in western practice …”
Section: Handling Of Niftp In Asian Practicementioning
confidence: 99%
“…As the majority of cases with indeterminate cytology are benign or borderline tumours, and the majority of thyroid carcinomas in indeterminate categories were low‐risk, clinical follow‐up of these nodules is one method recommended by the JTA clinical guidelines as long as they have benign clinical features …”
Section: Risk Stratification Of Patients With Indeterminate Nodules Amentioning
confidence: 99%
See 1 more Smart Citation
“…However, aggressive variants of PTC, for example, tall cell variant, medullary thyroid carcinoma (MTC), and distant metastatic carcinomas to the thyroid, although rare, may be diagnosed as FLUS or FN/SFN on FNA and should be included in the differential diagnosis . In a multi‐institutional review of 1,379 patients with FN undergoing surgical treatment, Conzo et al reported a final malignancy rate of 34% (469 cases), which included eight cases of MTC (0.6%) . Similarly, Hurthle cell lesions represent a distinct challenge to pathologists on FNA and iFS .…”
Section: Discussionmentioning
confidence: 99%
“…22 In a multi-institutional review of 1,379 patients with FN undergoing surgical treatment, Conzo et al reported a final malignancy rate of 34% (469 cases), which included eight cases of MTC (0.6%). 23 Similarly, Hurthle cell lesions represent a distinct challenge to pathologists on FNA and iFS. 24 Oncocytic changes may arise in benign conditions such as chronic lymphocytic thyroiditis, humoral-mediated hyperthyroidism, and multinodular goiters.…”
Section: Discussionmentioning
confidence: 99%